PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BACK TO NATURE BERBASIS INKUIRI TERBIMBING PADA MATERI INDIKATOR ALAMI ASAM DAN BASA KELAS VII MTS NEGERI 2 PONTIANAK - Yeni Meilani; Rini Muharini; Ira Lestari (EduChem, 2022)
This study aims was determine the level of eligibility of and response of students to the Back to Nature Student Worksheet based on guided inquiry based on natural and acid indicator materials developed. The form of research used is the Jarold Kemp development model. The sample selection technique for this study was stratified random sampling in 30 VII grade students of MTs Negeri 2 Pontianak. Data collection tools used are the feasibility assessment sheet and student questionnaire responses. The results of data analysis showed that the LKPD back to nature based on guided inquiry on natural and acidic natural indicator material was very feasible (81.58%). Students' responses to LKPD back to nature based on inquiry guided by natural and acidic natural indicator materials are very good (85.78%). The results of the feasibility assessment and student response test showed that LKPD back to nature based on guided inquiry on natural and acidic natural indicator material is very feasible to use in the learning process.Keywords: LKPD, natural indicators, acids and bases, guided inquiry, development